Tafsiran Lafadz Khusyu’ Perspektif Aisyah Bintu Syathi’ (Tinjauan Kitab al-Tafsir al-Bayani Lil Qur’anil Karim) - Nabila Nailil Amalia; Diana Durrotul Lum’ah; Asbarin (Jurnal test, 2023)
Interpretation of the meaning of the Qur'an is a study that is relevant to the present era, mufassir circles and intellectuals examine in detail the verses of the Qur'an with their respective styles of interpretation and methodology. Researchers also feel it is important to examine the meaning of the word khusyu' in terms of adabiyah or literature written by a female mufassir known as bintu syathi', the background and how the methods are used in interpreting verses about khusyu' contained in the Qur'an. The research method used is qualitative with the type of library research (library study) which is descriptive-analytical with a maudhu'i (thematic) approach. The data collection technique used is documentation. The analysis technique uses content analysis (content analysis). The result of this study is that the interpretation of the lafadz khusyu' in the book Al-Tafsir Al-Bayani Lil Qur'anil Karim shows that Bintu Syathi' draws several verses that explain the meaning of khusyu' into 2 parts, namely in the sense of khusyu'nya for believers because of the truth of faith to Allah and the Last Day, as stated in sura al-Baqarah: 45, Ali Imran: 199, al-Anbiya: 90 and al-Isra': 109 and al- Mu'minun: 2. Al-Ahzab: 25, al- Hadid:16. In addition, the meaning of khusyu' which means humility and humiliation, humiliation and fear is meant for infidels who do not believe in Allah SWT, namely in surahs Al-Nazi'at 8-9, Al-Ma'arij 43-44, Al- Qalam: 43, Al-Ghasiyah: 2, and Al-Qamar: 7.